Answer:
The values of "p" and "q" are p = -5 and q = -6
Step-by-step explanation:
Let's start by finding the zeroes of the polynomial 2x² - 5x - 3, and then we'll determine the relationship between these zeroes and the zeroes of x² + px + q.
The zeroes of a quadratic polynomial of the form ax² + bx + c can be found using the quadratic formula:
For the polynomial 2x² - 5x - 3, a = 2, b = -5, and c = -3. So, the quadratic formula becomes:
x = [-b ± √(b² - 4ac)] / (2a)
Substitute the values:
x = [-(-5) ± √((-5)² - 4(2)(-3))] / (2(2))
Simplify:
x = (5 ± √(25 + 24)) / 4
x = (5 ± √49) / 4
x = (5 ± 7) / 4
Now, we have two possible values for x:
x₁ = (5 + 7) / 4 = 12/4 = 3
x₂ = (5 - 7) / 4 = -2/4 = -1/2
So, the zeroes of 2x² - 5x - 3 are x₁ = 3 and x₂ = -1/2.
Now, we need to find the relationship between these zeroes and the zeroes of x² + px + q.
If the zeroes of x² + px + q are double in value to the zeroes of 2x² - 5x - 3, it means that for each zero "x" of 2x² - 5x - 3, there will be a corresponding zero "2x" for x² + px + q.
So, for x² + px + q, the zeroes will be 2 times the zeroes of 2x² - 5x - 3:
For x₁ = 3, the corresponding zero for x² + px + q is 2x₁ = 2(3) = 6.
For x₂ = -1/2, the corresponding zero for x² + px + q is 2x₂ = 2(-1/2) = -1.
Now, we have the zeroes of x² + px + q: 6 and -1.
To find "p" and "q," we can use Vieta's formulas. Vieta's formulas state that for a quadratic polynomial of the form ax² + bx + c with zeroes α and β:
α + β = -b/a
α * β = c/a
In our case, for x² + px + q with zeroes 6 and -1:
α + β = 6 - 1 = 5
α * β = 6 * (-1) = -6
Now, let's match these with the coefficients of x² + px + q:
α + β = 5, which corresponds to -p (since there's an "x" term in the middle)
α * β = -6, which corresponds to q (the constant term)
So, we have the following equations:
-p = 5
q = -6
Solve for "p" and "q":
p = -5
q = -6
So, the values of "p" and "q" are p = -5 and q = -6.
If the zeroes of the polynomial x² + px + q are double in value to the zeroes of 2x² - 5x - 3, find the value of p and q
Answer:
p and q are -5 and -6 respectively.
Step-by-step explanation:
factor
2x²-5x-3=0
(x-3) (2x + 1) = 0
x = 3, -1/2
multiply both by 2 = "double in value to the zeroes"
x = 6, -1
reverse factor them
(x-6)(x+1)
multiply
x2−5x−6
bard open bing claude perplexity generative AI
chegg brainly numerade course hero quizlet quiziz gathmath byjus
-The rays and the angle have two endpoints each.
-The rays and the angle have their lines extending in opposite directions.
-The rays have a number of points lying on them and the angle has only one point lying on it.
-The rays extend infinitely and the angle is made by the rays which have a common endpoint.
...?
Answer:
-The rays extend infinitely and the angle is made by the rays which have a common endpoint.
Step-by-step explanation:
A ray starts from one point and extends in one direction forever.
An angle is the space between two intersecting lines at or close to the point where they meet. In this case two rays intersect each other at one point
simplify the answer. this is extremely hard
Answer:
y = 1/3x+6
Step-by-step explanation:
Step 1
- Rewrite f(x) as y
f(x) = 3x-18 => y = 3x-18
Step 2
- Swap x and y
y = 3x-18 => x = 3y-18
Step 3
- Slove for y (By that it means isolate y)
x = 3y-18 (+18 both sides)
x+18 = 3y (Then divide both sides by 3)
1/3x+6 = y
Final Answer:
y = 1/3x+6
Volume of a cylinder: π * r^2 * h
Volume of a cone: 1/3 of the volume of a cylinder. V = π * r^2 * h/3
Explanation: r is the radius, h is the height, and if needed, you can use 3.14 for π
Answer:
The volume of a cylinder is: π × r2 × h
The volume of a cone is: 1 3 π × r2 × h
Answer:
15
Step-by-step explanation:
Answer:
True
Step-by-step explanation:
The ASA postulate applies. Angles at either end of the common segment are marked congruent. Thus the triangle are congruent.